The predictive value of the Singh index for the risk of InterTAN intramedullary fixation failure in elderly patients with intertrochanteric fractures - Zhe Xu; Guang Tian; Chen Liu; Yangjiang Xie; Ruguo Zhang (BMC Musculoskeletal Disorders, 2022)
Abstract Background To investigate the predictive value of the Singh index for the risk of InterTAN intramedullary fixation failure in elderly patients with intertrochanteric fracture to guide clinical treatment. Methods A total of 360 patients were divided into the Singh (I ~ II) (n = 120), Singh (III ~ IV) (n = 120) and Singh (V ~ VI) (n = 120) groups. Visual analog scale (VAS) and Harris scores were recorded at 1, 6, 12, 18 and 24 months after the operation. The correlation between the Singh index and the T-score of the total hip and femoral neck was analyzed. Logistic regression was used to analyze the relationship between the Singh index and internal fixation failure; the types of internal fixation failure were also analyzed. Results The Harris scores of the Singh (I ~ II) group were lower than those of the Singh (III ~ IV) and Singh (V ~ VI) groups 12, 18 and 24 months after surgery (P < 0.05). The Singh index was significantly correlated with the T-score of the total hip and femoral neck (P = 0.00, r = 0.89; P = 0.00, r = 0.83). The Singh (I ~ II) group had the lowest internal fixation survival rate within 24 months (P = 0.01). The Singh index was an independent predictor of internal fixation failure (P < 0.05). Lag screw cutting-out was the main type of internal fixation failure in the three groups (P = 0.00). Conclusion The Singh index is significantly correlated with the bone mineral density of the femoral neck and total hip. The Singh (I ~ II) group had lower Harris scores and a lower internal fixation survival rate than the other two groups. The Singh index is an independent predictor of internal fixation failure, especially lag screw cutting-out, after InterTAN fixation.